Clinical and economic analysis of empagliflozin therapy in patients with heart failure across the ejection fraction range - S. V. Nedogoda; A. S. Salasyuk; I. N. Barykina; V. O. Lutova; E. A. Popova (Российский кардиологический журнал, 2023)
Aim. To evaluate the cost-effectiveness of empagliflozin therapy in patients with heart failure (HF) across the ejection fraction (EF) range in the Russian Federation.Material and methods. An analysis of the cost of HF management was carried out and an analytical decision-making model was built in MS Excel, which makes it possible estimating the costs of HF management with empagliflozin from the state position.Results. Taking into account the direct costs of adverse events, as well as indirect costs, the potential economic benefit of empagliflozin use for 766028 HF patients with low EF could be RUB 7,6-7,8 billion per year of therapy, while for 5790280 patients with HF with moderately reduced and preserved EF — RUB 27,6-29,6 billion per year of therapy. The potential economic benefit of empagliflozin for 664960 patients with HF immediately after hospitalization for an HF exacerbation could be RUB 1,4-1,6 billion per year of therapy, allowing to prevent 69438 deaths and 60822 repeated exacerbations of HF.Conclusion. Empagliflozin is the optimal regimen for the treatment of patients with HF across the entire EF range, both with and without type 2 diabetes, both in terms of clinical efficacy of treatment and economic feasibility.